Visual eWOM Usefulness and Credibility: The Antecedents and Consequences - Whony Rofianto; Desta Atasyah Kornelys; Muhammad Rifkhansyah (Indonesia Banking School, 2017)
Nowadays the practice of spreading and utilizing eWOM increasingly prevalent. A lot of examination on eWOM effectiveness has been done, but it is still fragmented and overlook the potential of Visual eWom (VeWOM). Departing from the electronic word-of-mouth communication framework this research attempts to provide empirical evidence on the eWOM credibility-forming aspect and its implications toward eWOM adoption rate in the context of VeWOM video